P13.04 "I do feel like a scientist at time yeah…" acceptability of point-of-care testing for chlamydia and gonorrhoea to health service providers in remote primary care. (13th September 2015) - Natoli, L; Coburn, T; Maher, L; Shephard, M; Hengel, B; Badman, S; Causer, L; Tangey, A; Kaldor, J; Ward, J; Anderson, D; Guy, R
Abstract : Introduction: The GeneXpert test system is a molecular test used to diagnose Chlamydia trachomatis and Neisseria gonorrhoeae at the point-of-care (POC). It is being used in remote Aboriginal health services in Australia as part of the TTANGO (Test, Treat, ANd GO) Trial. Methods: In 2014 we interviewed 15 Aboriginal health workers/practitioners and nurses from 6 health services participating in TTANGO. Most were female (53%), 70% had worked >5 years in the remote sector and 40% were Aboriginal. We explored factors known to influence POC test acceptability including perceived ease of use and usefulness, and staff attitudes- which are all mediated by a range of barriers and enablers to POC test use. Results: Most staff found the GeneXpert both easy to use and useful in their setting. They indicated that POC testing has improved STI management, resulting in more timely and targeted treatment, earlier commencement of partner notification, and reduced time and effort associated with client recall. Staff expressed confidence in POC test results and in treating patients on this basis. They reported greater job satisfaction- feeling more in control of STI testing and patient health. Access to the GeneXpert appeared to legitimise or create an entry point to discussing STIs with clients, particularly for Aboriginal health workers. As most clients opted to return for test results (after 90 min) POC testing did not impact negatively on client flow. Managing positive test results in a shorter time frame was sometimes challenging. Manual documentation of results was considered to be onerous by some, who suggested that enhanced connectivity between the GeneXpert and patient management system could assist. Conclusion: Participants identified the potential for the GeneXpert to strengthen STI control in remote communities. Test acceptability was high, although some challenges remain and will inform future scale up/translation of POC testing in this setting. Disclosure of interest statement: No conflicts of interest declared. No financial support was received by Cepheid. Cepheid has provided GeneXpert devices on loan for the duration of TTANGO and test cartridges at a reduced rate.